Human induced pluripotent stem cells integrate, create synapses and extend long axons after spinal cord injury. Issue 7 (8th March 2022) - Lavoie, Nicolas Stoflet; Truong, Vincent; Malone, Dane; Pengo, Thomas; Patil, Nandadevi; Dutton, James R.; Parr, Ann M.
Abstract: Numerous interventions have been explored in animal models using cells differentiated from human induced pluripotent stem cells (iPSCs) in the context of neural injury with some success. Our work seeks to transplant cells that are generated from hiPSCs into regionally specific spinal neural progenitor cells (sNPCs) utilizing a novel accelerated differentiation protocol designed for clinical translation. We chose a xenotransplantation model because our laboratory is focused on the behaviour of human cells in order to bring this potential therapy to translation. Cells were transplanted into adult immunodeficient rats after moderate contusion spinal cord injury (SCI). Twelve weeks later, cells derived from the transplanted sNPCs survived and differentiated into neurons and glia that filled the lesion cavity and produced a thoracic spinal cord transcriptional program in vivo. Furthermore, neurogenesis and ionic channel expression were promoted within the adjacent host spinal cord tissue. Transplanted cells displayed robust integration properties including synapse formation and myelination by host oligodendrocytes. Axons from transplanted hiPSC sNPC‐derived cells extended both rostrally and caudally from the SCI transplant site, rostrally approximately 6 cm into supraspinal structures. Thus, iPSC‐derived sNPCs may provide a patient‐specific cell source for patients with SCI that could provide a relay system across the site of injury.